Efficient shape matching using shape contexts - Mori, Greg (IEEE transactions on pattern analysis and machine intelligence, 2005)
We demonstrate that shape contexts can be used to quickly prune a search for similar shapes. We present two algorithms for rapid shape retrieval: representative shape contexts, performing comparisons based on a small number of shape contexts, and shapemes, using vector quantization in the space of shape contexts to obtain prototypical shape pieces